Theory of the Avatar - Edward Castronova (Center for Economic Studies and ifo Institute (CESifo), 2003)
The internet has given birth to an expanding number of shared virtual reality spaces, with a collective population well into the millions. These virtual worlds exhibit most of the traits we associate with the Earth world: economic transactions, interpersonal relationships, organic political institutions, and so on. A human being experiences these worlds through an avatar, which is the representation of the self in a given physical medium. Most worlds allow an agent to choose what kind of avatar she or he will inhabit, allowing a person with any kind of Earth body to inhabit a completely different body in the virtual world. The emergence of avatar-mediated living raises both positive and normative questions. This paper explores several choice models involving avatars. Analysis of these models suggests that the emergence of avatar-mediated life may increase aggregate human well-being, while decreasing its cross-sectional variance. These efficiency and equity effects are contingent on the maintenance and protection of certain rights, however, including the right of agents to free movement, unbiased information, and political participation.
Keywords: 330; information and internet services; computer software; equity; justice; inequality; synthetic worlds